East Asian bond markets and economic growth - Rasidah Mohd Said (Penerbit Universiti Kebangsaan Malaysia, 2013)
Although the relationship between the stock market and growth has attracted many researchers, the number of studies that have been carried out into the links between debt and growth is very limited. This article examines the relationship between debt markets and economic growth. Three categories of debts are considered in this analysis, using data from China, Hong Kong, Japan, South Korea, and Thailand for the years 2002-2009. The results show that public and private debts have contributed significantly to the growth of the region. The significant contribution of debt markets to GDP, however, is not common for all the countries in the sample and varies according to the category of debts issued. Both public and foreign currency debts have contributed in a significantly positive way to South Korea’s GDP, but only public debt contributes in a significantly positive way to the growth of China and Hong Kong. As for Japan, none of the debt markets has had any impact on its GDP.